Evaluating the Role of Institutional Quality in the Relationship Between Education Expenditure and Manufacturing Growth: Insights from Quantile Regression Models - Al-Hasnawi, Maytham Hameed; Chin, Lee; Mazlan, Nur Syazwani; Niaz Ahmad, Mohd Naseem (Advances in Social Sciences Research Journal, 2024)
This study aims to provide empirical insight into the role of institutional quality and its impact on the relationship between expenditure on education and the growth of manufacturing in Malaysia. The study employed time series data from 1984 to 2020, using a quantile regression model for three quantiles: 25%, 50%, and 75%. The results showed that government spending on education (GXE) had a negative and statistically significant effect on manufacturing sector growth (MSG) on all quantiles in both interaction and non-interaction models. This may indicate a lack of quality, allocation, and efficiency in government expenditure and its targeting. However, the interaction effect between government spending on education and institutional quality (INTC GXE&IQI) on manufacturing sector growth (MSG) provided a consistently positive effect across all quantiles. This positive interaction means that the effect of education spending on manufacturing sector growth is conditional on the quality of institutions. The positive coefficients indicate that when government spending aligns with robust institutional frameworks, it effectively stimulates growth within the manufacturing sector. This phenomenon may be attributed to effective institutions amplifying the impact of government expenditure by ensuring efficient fund utilization for intended purposes. Policies aimed at strengthening institutions’ quality —such as improving bureaucracy, enhancing transparency, and combating corruption—can enhance the efficacy of education expenditure, which supports the long-term and sustainable growth of the manufacturing sector.